Metabolic cost of the effort specific to water polo game, based on the relationship between ph and lactic acid concentration in junior III - Marinescu, G.; Ticala, L. D.; Radulescu, A. (Science, Movement & Health, 2015)
Aim. To make a diagnosis of specific effort during the water polo game, in order to translate this effort towards some stimulating training means that are consistent with the requirements of competitive effort. The element of originality of our research is that there were tested and assessed, for the first time in the world, the demands to which junior III water polo players are subjected during the match. Methods. There were tested 6 athletes (junior III), components of the water polo team from "Steaua" School Sports Club no. 3, in an official match. We mention that, in order to objectively assess the demands, there were analyzed 27 biochemical parameters during the game progress ("interrupted trial") and after each quarter. The devices used were the Automatic blood gas analyzer ABL835 RADIOMETER and the Dry chemistry analyzer SPOTCHEM EZ Model SP-4430 - Arkray. In this paper, we chose to examine the evolution of two biochemical/ metabolic parameters: blood lactic acid (L.A.) and blood acid-base balance (pH). Methods used: test method, statistical and mathematical method - arithmetic mean, graphical method. Results. The average value of blood lactic acid concentration at the beginning of the match (basal metabolism) is 1.7 mmol; at the first break, the average value is 8.09 mmol of lactic acid; at the second break, the average value is 5.5 mmol of lactic acid; at the third break, the average value is 5.6 mmol of lactic acid, and at the end of the game, the average value is 6.2 mmol of lactic acid. In the "interrupted trial", the athlete C.D. recorded a value of 12.2 mmol of lactic acid following an effort specific to an attack phase (attack ended with a shot on goal, fallback, counterattack with a successful shot on goal). Conclusions. The highest L.A. value, 12.2 mmol of lactate recorded in the "interrupted trial", shows that the effort is performed within a lactate tolerance zone (S1) and, correlated to the lowest pH value, it shows that, during the exercises involving sprints, muscle glycogen (anaerobic glycolysis) generates a large amount of lactic acid and H+ ions, which results in a decrease of the pH value that may reach a level between 7.1 and 6.7 (see the lactic acid metabolism); consequently, the pH value of 7.238 is normal and falls within the tolerable limits for arterial blood, 6.9 to 7.5, because lactate has been measured in the blood, not in the muscles.